2022
DOI: 10.1172/jci153519
|View full text |Cite
|
Sign up to set email alerts
|

The epithelial-specific ER stress sensor ERN2/IRE1β enables host-microbiota crosstalk to affect colon goblet cell development

Abstract: Epithelial cells lining mucosal surfaces of the gastrointestinal and respiratory tracts uniquely express ERN2/IRE1b, a paralogue of the most evolutionarily conserved endoplasmic reticulum stress sensor ERN1/IRE1a. How ERN2 functions at the host-environment interface and why a second paralogue evolved remain incompletely understood. Using conventionally raised and germ-free Ern2 -/mice, we found that ERN2 was required for microbiota-induced goblet cell maturation and mucus barrier assembly in the colon. This oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 69 publications
4
28
0
Order By: Relevance
“…The lower endonuclease activity for ERN2 absence of ERN2, the expression of Xbp1s was reduced and Xbp1 -/mice showed a phenotype similar to that of Ern2 -/mice, proving that Xbp1 splicing induced by ERN2 was required for normal goblet cell function. Effects of the microbiota on the amount of Xbp1 have also been observed in other studies (10,13).…”
Section: Er Functions In Goblet Cellssupporting
confidence: 76%
See 3 more Smart Citations
“…The lower endonuclease activity for ERN2 absence of ERN2, the expression of Xbp1s was reduced and Xbp1 -/mice showed a phenotype similar to that of Ern2 -/mice, proving that Xbp1 splicing induced by ERN2 was required for normal goblet cell function. Effects of the microbiota on the amount of Xbp1 have also been observed in other studies (10,13).…”
Section: Er Functions In Goblet Cellssupporting
confidence: 76%
“…In this issue of the JCI, Grey and coauthors have continued to explore the function of ERN2 by using experimental animals (10). They nicely showed that Ern2-knockout mice had increased colon cell proliferation and elongated crypts as signs of mild spontaneous inflammation, which is similar to previous observations in Muc2-deficient mice (11).…”
Section: Goblet Cell Er Stress and Inflammationsupporting
confidence: 61%
See 2 more Smart Citations
“…Consistently, Grey et al showed that the gut microbiota determined the ERN2 expression, further inducing the maturation of goblet cells and the assembly of the mucus barrier. 13 Inconsistent with donor mice, there were no significant differences in the gene transcription levels of occludin, claudin-1, claudin-2, and ZO-1 among the three groups of recipient mice. Note that Snelson et al found that consumption of a heat-treated diet for 24 weeks resulted in increased intestinal permeability in rats (reversed by AGE inhibitors).…”
Section: Gos Regulate Intestinal Flora To Alleviate Age-induced Incre...mentioning
confidence: 82%